Profiling the volatile exometabolome of Pedobacter lusitanus NL19 - Figueiredo, Gonçalo André Henriques (2023)
The omics approaches, whether genomics, transcriptomics, proteomics and metabolomics constitute a set of excellent analysis tools that have been gaining relevance in the enormous amount of data generated and information provided. Metabolomics, defined as the detailed metabolome analysis, reveals the set of metabolites produced by a given organism, in a given condition and at a specific time/period of time. Microbial metabolomics is often used to provide information about the microbial metabolites produced by an organism, in a specific experimental environment/condition. Pedobacter lusitanus NL19 T (NL19 T ) has encoded in its genome, the information for the production of bioactive secondary metabolites (SMs). The range of compounds produced differs depending on the composition of the culture medium and this is particularly noticeable when the microorganism grows on PC 25%, a Tryptic Soy Broth (TSB) modified culture medium where the concentration of casein peptone is reduced to 25%. In addition, differences in the production profile of SMs were detected when compared to that of the phylogenetically close strain, Pedobacter himalayensis MTCC 6384T (MTCC 6384 T ), grown under the same conditions. Thus, the objective of this work is to understand the differences in volatile exometabolom es, of these two phylogenetically related species – strains NL19 T and MTCC 6384 T – in PC 25% and TSB 100%. To do so, we used the advantages of the combined HS -SPME/GC×GC -ToFMS methodology. A total of 325 compounds were identified. Of these, only 78 were considered statistically significant in the test conditions compared to the control conditions. 42 compounds differentiate the profile of the strains NL19 T and MTCC 6384 T in TSB100% and 11 differentiate the profile of the same strains in PC25%. The MTCC 6384 T strain has a greater abundance of compounds that are involved in the metabolism of pyruvate, amino acids, fatty acids, aromatic compounds and in the mevalonate pathway through geranylPP and farn e s ylPP. The detailed analysis of the compounds that present greater variability in the two media tested and for each strain identified 16compounds, of the metabolic pathways of amino acid and fatty acid metabolism and monoterpene biosynthesis. These present statistically different concentrations between the two media and in the two microorganisms. A second objective of this work was to understand if the volatile compounds (mVOCs) produced by NL19T strain, growing on TSB, interfere with the growth of Candida albicans I-11301. A new methodological approach made it possible to evaluate the effect of volatile compounds produced during the growth of strain NL19 in liquid medium with simultaneous growth of C. albicans on solid medium. At defined time intervals (24h, 48h, 72h, 96h, 120h and 144h) the emitted volatile compounds were analysed and the morphological changes in the yeast were observed. It was found that the mVOCs produced by NL19 T strain induce morphogenesis in C. albicans that assumes a filamentous morphology, possibly associated with virulence. The analysis of the mVOCs by HS -SPME/GC×GC - ToFMS under different conditions revealed the presence of 134 compounds, the majority of which are carbohydrates, ketones and alcohols . Of these, only 33 were analyzed in greater detail, as they increased or decreased significantly over time, and included mostly carbohydrates, ketones and sulfur - containing compounds and esters. The compounds were separated into two sets: set 2, which included compounds that gradually increase over time and set 3, which corresponds to compounds that increase sharply over a period of time but then decrease. It was on these sets that we focused our analysis since these could be the compounds that contributed to the phenotypic changes observed in C. albicans. Thus, this analysis suggests that the compounds 2 -methylnonane, 3 -methylbutyl - 2 -methylbutanoate, S -methyl 2 -methylpropanetioate, hexan - 2 - one, S -methyl 3 -methylbutanetioate, isopentyl formate and penta -1,2 -diene, which are produced in high quantities, may be responsible for inducing morphogenesis in C. albicans. This study allowed the beginning of the construction of the omics pipeline since it made it possible to have a preliminary approach on the metabolom es that could complement other approaches such as genomics, transcriptomics and proteomics.